The simulation of double inverted pendulum control based on particle swarm optimization LQR algorithm - Xin Xiong; Zhou Wan (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
The application of LQR controller in inverted pendulum system is common, but the choice of weight matrix Q and R of LQR controller has always been a difficult. This paper presents a new method to achieve the double inverted pendulum system LQR controller parameters optimization through the particle swarm optimization algorithm. The simulation result shows that the method used in the choice of matrix Q and R achieves very good results.